New Pyrazole‐ and Benzimidazole‐derived Ligand Systems. (16th April 2018) - Nozari, Mohammad; Addison, Anthony W.; Reeves, GorDan T.; Zeller, Matthias; Jasinski, Jerry P.; Kaur, Manpreet; Gilbert, Jayakumar G.; Hamilton, Clifton R.; Popovitch, Jonathan M.; Wolf, Lawrence M.; Crist, Lindsay E.; Bastida, Natalia
Abstract : A series of N‐ containing heterocyclic compounds have been synthesized using approaches such as the well‐known Knorr synthesis, and a facile N ‐alkylation method. This series of compounds includes pyrazole derivatives, tris(2‐benzimidazolylmethyl)amine derivatives, and "pincer" ligands. Characterization methods include 1 H NMR, FT‐IR, CHN analyses, UV‐vis spectroscopy, and fluorimetry, while X‐ray crystal structures are reported for most of the compounds. The crystallographic results affirm a 13 C NMR method for isomer assignment of substituted pyrazoles. Abstract :